EFFECTIVE COMMUNICATION AS THE BASIS OF PERSONNEL MANAGEMENT - BAHAN, Nadiia; DIACHENKO, Yuliia; KORINNA, Anastasiia; TOKAR, Kateryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the importance of effective communication as the main tool of personnel management in modern enterprises. The key aspects of the communication process that affect employee productivity, motivation level and corporate culture are identified. The impact of digitalization, corporate culture and soft skills development on the quality of managerial communication is studied. The types of communications in personnel management are analyzed and the main problems that arise in the process of information exchange in organizations are identified. It is proven that an established communication system contributes to improving coordination of actions, quick decision-making and reducing the level of conflict. The main features of effective communication are the active participation of employees in the process of information exchange, their willingness to cooperate and the ability to work with large volumes of data. Important factors are also an informal style of communication, an atmosphere of trust in the team, the use of modern communication technologies, an extensive network of communication channels, a favorable socio-psychological climate and the efficiency of information dissemination. The need to implement modern communication methods and technologies (CRM systems, corporate portals, messengers) to increase the efficiency of management processes is substantiated. It is determined that the communication competence of managers is a strategic factor in building trust in the team, increasing staff motivation and ensuring the long-term success of the organization. Research indicates that effective communication contributes to improving corporate culture, increasing staff loyalty and creating a favorable climate in the team. It is important to invest in the development of communication skills of managers, because they set the tone for corporate culture and determine the success of the organization in the long term.
Keywords: personnel; communication; personnel management; corporate culture; communication competence